Prognosis in Pregnant Females With Systemic Lupus Erythematosus - Enling LIU; Yuxiu ZHOU (Archives of Rheumatology, 2017)
Objectives: This study aims to analyze the relationship between pregnancy and lupus, and explore the risk factors that adversely affect maternal and infant outcomes. Patients and methods: The pregnancy outcomes in 112 pregnant females (mean age 24.3±2.8 years; range 20 to 35 years) with systemic lupus erythematosus (SLE) were retrospectively analyzed. Pregnancy outcomes before and after pregnancy were compared, and the associations with lupus nephritis, positive anti-Ro/SSA antibody, positive La/SSB antibody, complement 3 and complement 4, high blood pressure, positive anti- cardiolipin (aCL) antibody, Raynaud’s phenomenon, and lupus recurrence were evaluated. Factors contributing to adverse outcomes were analyzed using multinomial logistic regression. Results: The live birth rate in females diagnosed with SLE before a pregnancy was higher than that in females diagnosed with SLE after a pregnancy. The fetal mortality rate in females diagnosed with SLE after a pregnancy was higher than that in females diagnosed with SLE before a pregnancy. However, the abortion rate in females diagnosed with SLE before a pregnancy was also significantly higher than that in females diagnosed with SLE after a pregnancy. The incidence of preterm birth in females diagnosed with SLE after a pregnancy was higher than that in females diagnosed with SLE after a pregnancy. Preterm birth was more likely to occur in females positive for Ro/SSA antibody. Patients with hypertension and Raynaud’s phenomenon had a higher risk of intrauterine growth retardation. In addition, the presence of aCL antibody was associated with pregnancy loss. Multinomial logistic regression analysis showed that many factors might be associated with adverse pregnancy outcomes, including lupus nephritis, positive Ro/SSA antibody, positive La/SSB antibody, complement 3 and complement 4, positive aCL antibody, lupus recurrence, hypertension, and Raynaud’s phenomenon. Conclusion: Lupus nephritis, Ro/SSA antibody, aCL antibody, hypertension, Raynaud’s phenomenon, and lupus recurrence are important factors associated with adverse pregnancy outcomes.